The role of cellular senescence in metabolic diseases and the potential for senotherapeutic interventions - Zhang, Huantong; Zhou, Han; Shen, Xin; Lin, Xingchen; Zhang, Yuke; Sun, Yiyi; Zhou, Yi; Zhang, Lei; Zhang, Dayong (Frontiers in Cell and Developmental Biology, 2023)
Cellular senescence represents an irreversible state of cell cycle arrest induced by various stimuli strongly associated with aging and several chronic ailments. In recent years, studies have increasingly suggested that the accumulation of senescent cells is an important contributor to the decline of organ metabolism, ultimately resulting in metabolic diseases. Conversely, the elimination of senescent cells can alleviate or postpone the onset and progression of metabolic diseases. Thus, a close relationship between senescent cells and metabolic diseases is found, and targeting senescent cells has emerged as an alternative therapy for the treatment of metabolic diseases. In this review, we summarize the role of cellular senescence in metabolic diseases, explore relevant therapeutic strategies for metabolic diseases by removing senescent cells, and provide new insights into the treatment of metabolic diseases.